State bureau of investigation (SBI) and Federal bureau of investigation (FBI): comparative analysis of certain elements of administrative and legal status - Shmilo , Nazar (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article deals with the issue of administrative and legal status of such law enforcement agency as the State Bureau of Investigation. The author emphasises that the legal status of the SBI is rather complicated, given that it is a central executive body with a special status. At the same time, this state body is a law enforcement agency, as it is vested with law enforcement functions. Given such a complex nature of this state body, an attempt was made to conduct a comparative analysis of the SBI's administrative and legal status with a similar analogue of the United States of America - the Federal Bureau of Investigation, which will allow to adopt positive practices in the SBI's activities. It is established that the correct determination of the SBI's place in the system of law enforcement agencies of Ukraine and its administrative and legal status is somewhat dependent on a comparative analysis with other analogues in the world, in particular, with the Federal Bureau of Investigation (USA). The SBI itself is very similar to the FBI in terms of its tasks and powers. The author concludes that the FBI is the main investigative agency of the US Department of Justice and a full member of the US intelligence community. The FBI has the authority and responsibility to investigate specific crimes assigned to it and to provide other law enforcement agencies with shared services such as fingerprint identification, laboratory testing and training. The FBI also collects, shares, and analyses intelligence to support its own investigations and those of its partners, as well as to better understand and combat the security threats facing the United States. The history of the creation of the BR and the SBI was analysed. Based on the findings, the study provides recommendations for improving the administrative and legal status of the SBI.